A formação continuada de professores da educação infantil e a relação com a prática pedagógica: no sistema municipal de ensino de Guarapuava – Paraná - Silva, Melissa Rodrigues da (2011)
This research this tying with the Program of Post-Graduation in Education of the Tuiuti University of the Paraná and integrates the studies of the Pedagogical Practical line of research of and Articulators Elements. The problem of the research had its origin in function of the teaching work in the graduation in Pedagogy and of the dialogue kept with pupils who acts in the Infantile Education, either as trainees or staff that presents some questionings in the performance with small children. Articulated about the initial formation this work of research in analyzing the continued formation of the professors was worried who act in the Centers of Infantile Education in the city of Guarapuava - PR. The general objective thus is enunciated: To analyze the continued formation, implemented for the public politics of the Secretariat of the Education, for professors who act in the Centers of Infantile Education of Guarapuava - PR. The specific objectives: to describe the project of formation continued for Infantile Education, in its aspects of elaboration, structure, planning, objectives, thematic, participation of the professors; to analyze the proposal, the organization and the accomplishment of the formation continued for the professors of the Infantile Education in the city of Guarapuava - PR; to understand the specific formation for the professors who act in the Centers of Infantile Education, with sights to the practical professor and the formation of the child as a historical and social being; and to detect the paper of the initial formation while base for the continued formation. It was opted to the qualitative boarding. The methodological procedure used questionnaires with approach of the practical professor of the professionals who already act to some time in Infantile Education and, also, of the trainees who had not yet finished the course or the course of formation of professors superior (average level); and interviews carried through with the Municipal Secretary of Education, the Administrative Coordination of the Infantile Education and with the pedagogical team of each institution. We give to emphasis and importance to the initial formation in Pedagogy, and also the continuation of this. The study it was carried through in five Centers of infantile Education, that take care of to children of 4 months the 5 years of age, and amongst these, we detach some differentiations in its localization and organization. The theoretical and methodological recital was searched in authors, as: Arce (2007), Cerisara (2002, Kramer (2003), Kuhlmann Jr (1998), Libâneo (2005), Nicholas (2002), Oliveira (2010), Saviani (1991, 2005, 2007), among others. The research searched in the Infantile the scene of the construction and pedagogical reflection of practical, local Education the rich one in experiences, quarrels and construction of knowledge; and, also, in the construction of the child as social, deserving one to be of cares and an education of quality.